2020
DOI: 10.1029/2020wr027582
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Effects on Flow and Salinity Distributions in Coastal Confined Aquifers

Abstract: Coastal aquifers provide an important hydrologic connection between terrestrial freshwater and oceanic seawater. Understanding the water flow and salinity distributions in those aquifers is essential to manage seawater intrusion and regional groundwater resources. For the last 50 yr, these processes have been extensively examined; however, previous studies typically assumed isothermal conditions and overlooked groundwater-seawater temperature contrasts, as commonly found along the global coastline. Here, we va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(28 citation statements)
references
References 77 publications
(118 reference statements)
5
23
0
Order By: Relevance
“…It has been established that external forces acting on the landward and seaward boundaries, for example, the tidal stage (Henderson et al., 2010), tidal amplitude (Abarca et al., 2013), seawater temperature (Befus et al., 2013; Nguyen et al., 2020; Pu et al., 2020), rainfall (Yu et al., 2017), and inland hydraulic gradient (Kuan et al., 2012; Yu, Xin, & Lu, 2019), influence the USP configuration. These forces operate at various timescales, such as seasonal or daily seawater temperatures (Anderson, 2005), spring‐neap tides with different amplitudes (Robinson, Gibbes, et al., 2007), and seasonality in inland hydraulic gradients (Liu et al., 2016), thus, creating a dynamic intertidal environment.…”
Section: Introductionmentioning
confidence: 99%
“…It has been established that external forces acting on the landward and seaward boundaries, for example, the tidal stage (Henderson et al., 2010), tidal amplitude (Abarca et al., 2013), seawater temperature (Befus et al., 2013; Nguyen et al., 2020; Pu et al., 2020), rainfall (Yu et al., 2017), and inland hydraulic gradient (Kuan et al., 2012; Yu, Xin, & Lu, 2019), influence the USP configuration. These forces operate at various timescales, such as seasonal or daily seawater temperatures (Anderson, 2005), spring‐neap tides with different amplitudes (Robinson, Gibbes, et al., 2007), and seasonality in inland hydraulic gradients (Liu et al., 2016), thus, creating a dynamic intertidal environment.…”
Section: Introductionmentioning
confidence: 99%
“…FW-SW temperature contrasts have been widely reported around global coastlines (Wilson, 2005;Befus et al, 2013;Paldor et al, 2020;Pu et al, 2020). Temperature could alter the fluid density and viscosity in coastal aquifers, regulating density-driven flow and FW-SW mixing processes (van Lopik et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Temperature could alter the fluid density and viscosity in coastal aquifers, regulating density-driven flow and FW-SW mixing processes (van Lopik et al, 2015). Salinity distributions and groundwater discharge could thus be significantly regulated as the thermal regime changes in coastal aquifers (Nguyen et al, 2020;Pu et al, 2020). Wilson (2005) pointed out that geothermal convection could be developed in regional-scale coastal flow systems, contributing to the saline submarine groundwater discharge.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Temperature is an important control on groundwater flow and biogeochemical activity in shallow unconfined aquifers due its effect on fluid viscosity and microbial reaction kinetics. Pu et al (2020) conduced laboratory tank experiments and used numerical variable-density flow and heat transport models of an unconfined coastal aquifer without tidal influence and showed that the saltwater-freshwater interface shifted seaward with an increase in seawater temperature or a decrease in fresh groundwater temperature. Temperature controls on flow and salt transport have also been investigated in beach aquifers.…”
mentioning
confidence: 99%